Kajian Tingkat Potensi Pariwisata dalam Upaya Mitigasi Bencana di Kecamatan Belik Kabupaten Pemalang - Utbah Aminatul Hofisah; Esti Sarjanti; Suwarsito Suwarsito (UM Purwokerto Press, 2022)
The development of tourism programs in Indonesia is getting more attention with the Wonderful Indonesia program, as well as tourism in Belik District, Pemalang Regency. This study aims to determine the level of tourism potential as a disaster mitigation effort in Belik District, Pemalang Regency. This survey research was conducted to obtain tourism potential data in the form of 5 (five) components of tourism which include the quality of tourism objects, condition of tourism objects, object development support, accessibility, and object supporting facilities. The population is a tourist attraction which amounts to 6 attractions. The sampling technique was carried out by a total sampling of 6 tourist objects. Data collection uses a checklist sheet of tourism components based on the 2016 Pemalang Regency Tourism Development Master Plan (RIPPDA) with modifications. Data processing using scoring. Analysis of tourism potential data is categorized into 3 classes, namely low, medium and high. The results showed that of the 6 (six) tourism objects studied, there were 2 (two) levels of tourism potential, namely low potential and medium potential. The level of tourism potential is moderate in 4 (four) tourist objects, namely Mendelem Hill (Taman Rancah), Batur Candi Tourism, Bengkawah Waterfall, and Jambe Twin Baths. The low potential level is found in 2 (two) tourism objects, namely Silating Lake and Barong Curug. The dominance of the tourism potential level of the medium category in the form of natural tourism objects can still be developed by taking into account the aspects of disaster mitigation.